PkM Peningkatan Nilai-Nilai Pendidikan Karakter dalam Kegiatan Belajar Mengajar di Pesantren Mizanul Ulum Sanrobone Takalar - Surani, Surani; Darmawangsa, Andi; Ardi, Ardi (Penerbit Goodwood, 2024)
Purpose: The main purpose of the Community Service Activity (PKM) is to make a significant contribution to strengthening the character of teachers in the environment of Mizanul Ulum Sanrobone Islamic Boarding School, Takalar. The specific focus on